2007
DOI: 10.1105/tpc.106.041426
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis PLDζ2Regulates Vesicle Trafficking and Is Required for Auxin Response

Abstract: Phospholipase D (PLD) and its product, phosphatidic acid (PA), play key roles in cellular processes, including stress and hormonal responses, vesicle trafficking, and cytoskeletal rearrangements. We isolated and functionally characterized Arabidopsis thaliana PLDz2, which is expressed in various tissues and enhanced by auxin. A PLDz2-defective mutant, pldz2, and transgenic plants deficient in PLDz2 were less sensitive to auxin, had reduced root gravitropism, and suppressed auxindependent hypocotyl elongation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
141
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(160 citation statements)
references
References 84 publications
15
141
2
Order By: Relevance
“…Thus, for a particular cell file within the arabidopsis root, the TD can also be defined as the region where cells endoreduplicate and continue elongating at the same rate as in the PD. It has also been shown that phospholipase Df2, involved in vesicle trafficking, is strongly expressed in the transition zone (Li and Xue, 2007;Mancuso et al, 2007). The MSC analysis used here clearly shows that before the onset of rapid elongation all cells within a file, irrespective of the tissue type, are distributed in two subsets separated by an identifiable transition: those in the PD and those in the TD.…”
Section: Discussionmentioning
confidence: 52%
“…Thus, for a particular cell file within the arabidopsis root, the TD can also be defined as the region where cells endoreduplicate and continue elongating at the same rate as in the PD. It has also been shown that phospholipase Df2, involved in vesicle trafficking, is strongly expressed in the transition zone (Li and Xue, 2007;Mancuso et al, 2007). The MSC analysis used here clearly shows that before the onset of rapid elongation all cells within a file, irrespective of the tissue type, are distributed in two subsets separated by an identifiable transition: those in the PD and those in the TD.…”
Section: Discussionmentioning
confidence: 52%
“…In this sense, with regards to the role of PLD2 under the initial stage of phosphate deprivation and PLD2 tonoplast localization (12,22,33,40,41), PA produced by PLD2 could be a switch related to phosphate sensing. Formation of prokaryotic PA could also be important for MGD1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although many pieces of evidence have indicated the crosstalk between the PI signaling pathway and auxin signaling pathway via regulation of auxin homeostasis or auxin transport [12,42,[49][50][51], the potential link of PIP5K with auxin-related processes has not yet been directly investigated. Here we report on the functional characterization of Arabidopsis PIP5K2, which is expressed in various tissues and whose expression is enhanced by exogenous auxin.…”
Section: Introductionmentioning
confidence: 99%